Pendidikan Kesehatan Melalui Media Leaflet Tentang Perilaku Hidup Bersih Dan Sehat (Phbs) Terhadap Pengetahuan Masyarakat Desa Sungai Raya Rt/Rw 001/004 Kelurahan Sembulang Kecamatan Galang - Fitri Nur Indriani; Nurhafizah Nasution; Mutia Amalia Lubis; Sri Nuraeni; Sofia Nurfitriani (Pusat Riset dan Inovasi Nasional, 2021)
There is still low awareness of Clean and Healthy Living Behavior (PHBS) and there are still many people who have not implemented (PHBS) in their daily lives. Uapaya (PHBS) if not carried out by every family and family members will be a risk factor that can cause diseases such as intestinal worms, diarrhea, skin diseases, and malnutrition. Clean and Healthy Living Behavior is basically an effort to pass on experiences on Clean and Healthy Living behavior through individuals, groups or the wider community with communication channels as a medium for sharing information to increase public knowledge. The purpose of this study was to determine the effect of the effectiveness of counseling and training through leaflet media on the knowledge of the Sungai Raya village community. This study used a quasi-experimental research design with a quasi-experimental one group pretest-posttest design. With a total sample of 20 samples using paired t-test statistics. From the results of this study it can be seen that there is a difference in the average knowledge of the community after counseling and training is carried out with a p value of 0.000 that there is an influence of counseling using leaflet media Keywords: , ,